HYDROGEOLOGICAL INDICATIONS OF RECENT MOVEMENTS OF THE EARTH'S CRUST - Kissin I.G.; Orolbaev E.E. (My University, 1988)
Hydrogeologic indications of recent movements of the Earth's crust in two regions of North Tian-Shan have been studied. Comparison of ground-water level changes and variations of recent vertical movements according to benchmarks located near a well demonstrates their good correlation. The ground-water level varies out of phase with the direction of vertical movements. A correlation between level variation and seismic regime has been observed up to a well, located in a near-fault zone. In the region of the Kochkorskaya Depression, well observations show that against a background of constant increasing of level, sharp decays are observed. The latter can be connected with creep displacements. Hydrogeologic observations, together with periodic levelling enable us to study recent movements of the Earth's crust in detail.